2013
DOI: 10.1016/j.catena.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire on soil organic matter quality along an altitudinal sequence on Mt. Etna, Sicily

Abstract: Soil organic matter (SOM) can directly be affected by wildfires, both in terms of quantity and quality. The combustion is often incomplete, leading to the formation of pyrogenic organic matter (PyOM), a highly heterogeneous material with prevailing aromatic nature. Focusing our attention on PyOM, we investigated an altitudinal soil sequence on Mount Etna, Italy, ranging from 500 m to 1800 m asl, where the fire frequency is assumed to have been higher at lower elevations due to a warmer and drier climate. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…Because of the important role of litter as a source of SOM for mineral soil, accumulation of pyrogenic recalcitrant organic compounds determines the long-term SOM content, SOM properties and C-sequestration capacity of the soil (Knicker et al, 2012;Mastrolonardo et al, 2013). The data from elemental and thermal stability analyses confirm previous reports suggesting that the charred biomass generated in wildfire may not be stable in the long term (e.g.…”
Section: Implications For Soil Conservation After Wildfiresupporting
confidence: 82%
See 2 more Smart Citations
“…Because of the important role of litter as a source of SOM for mineral soil, accumulation of pyrogenic recalcitrant organic compounds determines the long-term SOM content, SOM properties and C-sequestration capacity of the soil (Knicker et al, 2012;Mastrolonardo et al, 2013). The data from elemental and thermal stability analyses confirm previous reports suggesting that the charred biomass generated in wildfire may not be stable in the long term (e.g.…”
Section: Implications For Soil Conservation After Wildfiresupporting
confidence: 82%
“…Thus, Santín et al (2012) observed large differences in the abundance of charred biomass in rainforest and eucalypt forests. Mastrolonardo et al (2013) also attribute the amount and chemical nature of the burnt litter to changes in the vegetation. This variability may also explain differences in short-term microbial responses found in different ecosystems after burning (Bárcenas-Moreno et al, 2013).…”
Section: Implications For Soil Conservation After Wildfirementioning
confidence: 98%
See 1 more Smart Citation
“…plants with waxcoated leaves, which naturally induce water repellent properties to soil (Lozano et al 2013). As a consequence, PyOM formed here at relatively low temperatures may indeed have a large contribution from aliphatic compounds (Knicker et al 2005b;Mastrolonardo et al 2013). This could have many ecological implications.…”
Section: Discussionmentioning
confidence: 98%
“…In the last decades, the role of PyOM in biogeochemical cycles has received much attention since several forms of PyOM are recalcitrant to both biotic and abiotic degradation; thus, PyOM acts as an important inert carbon reservoir in the global carbon cycle (Schmidt and Noack 2000). PyOM was studied using several different methods, such as vibrational or magnetic spectroscopy (Almendros et al 2003;Knicker et al 2006;Francioso et al 2011;Mastrolonardo et al 2013), thermal analysis (De la Rosa et al 2008;Mastrolonardo et al 2014), visual microscopy (Stoffyn-Egli et al 1997;Pituello et al 2014) and chromatographic analyses (De la Rosa et al 2008;Nocentini et al 2010). Nevertheless, the nature of PyOM remains to be fully understood.…”
Section: Introductionmentioning
confidence: 99%